Environmental behavior of waste rocks based concrete: Leaching performance assessment. (December 2021) - Taha, Y.; Benarchid, Y.; Benzaazoua, M.
Abstract: The reuse of mine waste rocks as construction material is an innovative and sustainable management technique that can lower their surface disposal, mitigate their environmental impacts and provide opportunity to conceive economic benefits. However, the implementation of this approach is still limited due principally to insufficient knowledge on environmental behavior of mine wastes-based products. This paper aims in investigating these issues by assessing the leaching behavior of two low sulfide-mining waste rocks suitable for concrete production. Concentrations of inorganic contaminants released from single waste rocks were measured by means of weathering cell, CTEU-9, TCLP and SPLP tests. Compressive strength and immobilization performance of obtained concretes based on these waste rocks were assessed. The results of humidity cell tests indicated that waste rock with higher sulfur content (0.47 wt%) and lower carbon content (0.26 wt%) did not present an acid generating potential according the Quebec environmental regulation. Those of TCLP, SPLP and CTEU-9 batch tests showed a concentration of contaminants in leachate solutions from waste rocks below the standardized limits fixed by the Environmental Protection Agency. Concretes made using these waste rocks as aggregates exhibited a suitable compressive strength. Concentration of heavy metals and sulphates released from concretes using tank-leaching test were under the limit requirements fixed by the Soil Quality Decree. Highlights: Physico-mechanical properties of concretes incorporated with waste rocks are discussed. Leachates from waste rocks are analyzed by TCLP, SPLP, CTEU-9 and humidity cells tests. Leachates from waste rocks based concretes were investigated using monolithic leaching test. Heavy metals and metalloids were immobilized in the concrete matrix.